Survival of acid-adapted and non-adapted Shiga toxin-producing Escherichia coli using an in vitro model. (October 2019) - Rivera-Reyes, Minerva; Campbell, Jonathan A.; Cutter, Catherine N.
Abstract: Shiga toxin-producing Escherichia coli (STEC) are known to adapt and survive acidic conditions. Acid-adaptation also may result in cross-protection against other stressors present in foods, such as reduced water activity (aw ), refrigeration conditions, or the presence of antimicrobials. Three independent experiments were conducted with non-adapted (control) and acid-adapted E. coli O157:H7 and non-O157:H7 serogroups ( E. coli O26, O45, O103, O111, O121 and O145) in vitro and in situ. Experiment 1: STEC cocktails in media were left untreated (non-adapted; control) or adapted (pH 5.0), exposed to mild acidic conditions (pH 4.5) or reduced aw (0.88 and 0.75) for 4 days at 24 °C, and evaluated for survival. Experiment 2: Non-adapted and acid-adapted STEC cocktails were subjected to desiccation (28 days at 24 °C) on sterile paper disks, and remaining pathogen populations were determined. Experiment 3: Control and acid-adapted STEC were subjected to mild acidic conditions (pH 4.5) and low aw (0.88 or 0.78) in ground beef slurries (GBS; 4 days at 24 °C) and surviving populations enumerated. Results from experiment 1 demonstrated that populations of non-O157:H7 STEC serogroups O45, O103, O111 and O121 were significantly different from populations of E. coli O157:H7, and non-O157:H7 STEC serogroups O26 and O145. In contrast, when STEC serogroups were acid-adapted, all populations of non-O157:H7 STEC were significantly different from populations of E. coli O157:H7. Results of experiments in media with aw of 0.88 or 0.78 demonstrated that there was no significant difference between E. coli O157:H7 and any of the non-O157:H7 STEC, regardless of acid-adaptation. In experiment 2, exposure to desiccation resulted in no significant difference in survival between E. coli O157:H7 and non-O157:H7 STEC, regardless of acid-adaptation. Experiment 3 in acidified GBS demonstrated that all non-O157:H7 STEC behaved similarly to E. coli O157:H7, except for E. coli O145, which had a higher reduction than O157:H7. There were no significant differences in bacterial populations associated with GBS with modified aw . Collectively, these results suggest than non-O157:H7 STEC behave similarly to E. coli O157:H7 when exposed to low pH (<4.5) and low aw (0.88 or 0.78) under laboratory conditions. Highlights: STEC are known to adapt and survive acidic conditions In vitro and in situ experiments were conducted with acid-adapted STEC Non-O157:H7 STEC behave similarly to E. coli O157:H7 Behavior of pathogens were similar under low pH and aw